Mencermati Sejarah Perkembangan Filsafat Islam - A. Khudori Soleh (Universitas Darussalam Gontor, 2014)
Although acknowledged that Greek philosophy gave great influence on the development of Islamic philosophy, but philosophy of Islam are not based on it, because; (1) to learn does not necessarily reflect a repetition, (2) every thought is not separated from their cultural context, (3) the real fact shows that Islamic rational thinking has established before the arrival of Greek philosophy. If so, where Islamic philosophical thought come from? The answer is from the Islamic tradition itself, from scientists who attempt to explain the teachings of the Muslim holy book. There are three measures relevant to philosophical reasoning: ta’wil method, explanation of musytarak meaning, and qiyâs. In addition, the demands on theological issues, to harmonize the views that seem contradictory and complex, for further systematized it in an integral metaphysical idea. From there developed methods and philosophical thought in Islam, long before the arrival of Greek philosophy through the process of translation. First of all it was accepted because it is needed to answer new problems which require rational thinking, then it was declined at the time of Ibn Hanbal because there are certain cases which considered deviant, it was developed again in the time of al-Farabi and Ibn Sina, then rejected and considered to cause disbelief in the al-Ghazali era, and it was developed again at the Ibn Rushd, then change lanes to work together with Sufism in the time of Suhrawardi and Ibn Arabi. Finally, tradition of philosophical thought in the Sunni world does not grow up but remains develop well within the Shiite community.